Palladium-Catalyzed Direct C-2 Arylation of Indoles with Aryl Halides in Aqueous Medium - Lu, Guo-ping; Cai, Chun (Synlett, 2012)
A newly developed, efficient catalytic system for direct C2-arylation of indoles with aryl halides in aqueous medium under mild conditions (80 °C) is reported. These procedures are free of toxic solvents, and exhibit improved yields and high chemo- and regioselectivity.
Keywords: arylation; indole; aqueous medium; green chemistry; synthetic method